600 km/h moving model rig for high-speed train aerodynamics. Issue 227 (August 2022) - Yang, Ming-zhi; Zhong, Sha; Zhang, Lei; Qian, Bo-sen; Wang, Tian-tian; Zhou, Dan; Wu, Fan
Abstract: A maglev train with a speed of 600 km/h or higher can fill the speed gap between civil aircrafts and wheel rail trains to alleviate the contradiction between the existing transportation demand and actual transport capacity. However, the aerodynamic problems arising due to trains running at a higher speed threaten their safety and fuel efficiency. Therefore, we developed a newly moving model rig with a maximum speed of 680 km/h to evaluate aerodynamic performance of trains, thus determining the range of the aerodynamic design parameters. In the present work, a launch system with a mechanical efficiency of 68.1% was developed, and a structure of brake shoes with front and rear overlapping was designed to increase the friction. Additionally, a device to suppress the pressure disturbances generated by the compressed air, as well as a double track with the function of continuously adjusting the line spacing, were adopted. In repetitive experiments, the time histories of pressure curves for the same measuring point are in good agreement. Meanwhile, the moving model test and full-scale experimental result of maglev trains passing each other in open air are compared, with an error less than 4.6%, proving the repeatability and rationality of the proposed moving-model. Highlights: Maximum speed of 680 km/h moving rig model is designed and established. Launch system with a high test speed and mechanical efficiency. Braking system adopts brake shoes with front and rear overlapping to enhance friction. Development of device that suppresses the pressure disturbances due to compressed air.